2015
DOI: 10.1159/000441849
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Valproic Acid on Neuroendocrine Tumour Cells

Abstract: Background/Aims: Histone deacetylases (HDACs) modulate lysine acetylation on histones and are frequently deregulated in cancer. HDAC inhibitors with potent anti-tumour effects have been developed and are now being tested in clinical trials. The aim of this study was to investigate the effects of valproic acid (VPA), an inhibitor of class I and class IIa HDACs, on neuroendocrine tumour (NET) cell growth. Methods: Three NET cell lines, GOT1 (small intestinal), KRJ-I (small intestinal), and BON (pancreatic), were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 45 publications
4
23
0
Order By: Relevance
“…These data suggested that MTX and VPA severely affected neural and RG commitment. In addition, as expected [ 39 , 40 ], both drugs negatively impacted cell proliferation, as shown by a decrease on the amount of Ki67 + cells.…”
Section: Discussionsupporting
confidence: 81%
“…These data suggested that MTX and VPA severely affected neural and RG commitment. In addition, as expected [ 39 , 40 ], both drugs negatively impacted cell proliferation, as shown by a decrease on the amount of Ki67 + cells.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are consistent with other in vitro cancer studies, which have demonstrated IC 50 ranging from 3–10 mM for ovarian and uterine sarcoma cells, and 4.5–8 mM for thoracic (oesophageal and non-small cell lung) cancer cells [29, 30]. Much lower cytotoxic IC 50 of 0.89–1.92 mM have been noted in neuroendocrine tumours, but this required drug exposure times of up to seven days [31]. …”
Section: Discussionsupporting
confidence: 90%
“…DNA methylases inhibitor and HDAC inhibitor have been extensively used in vitro in both PanNET and small intestine cell lines showing results in terms of reducing cell viability and increasing gene expression (Baradari et al 2006, Habbe et al 2007, Alexander et al 2010, Arvidsson et al 2016. Interestingly, Decitabine increased the expression of SSTR2 and the Ga-DOTATOC uptake in BON1 tumour-bearing mice, indicating a possible therapy implication in re-expression the target for somatostatin receptor-based radiotherapy (Taelman et al 2016).…”
Section: Clinical Implicationmentioning
confidence: 99%